2006
DOI: 10.1021/cm0616331
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Morphology of Poly(isobenzofuran) Films Grown by Hot-Filament Chemical Vapor Deposition

Abstract: We describe hot-filament chemical vapor deposition of poly(isobenzofuran) (PIBF) films and characterize their chemical structure and surface morphology. The precursor monomer, 1,2,3,4-tetrahydro-1,4epoxynaphthalene, is pyrolyzed by flowing it over an array of hot filaments held at three different temperatures (680, 738, and 800 °C). The produced intermediate, isobenzofuran (IBF), is deposited onto a silicon substrate as thin films of PIBF. Fourier transform infrared spectroscopy and X-ray photoelectron spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the absence of a plasma, the large energetic barrier to creating charged species in the gas phase guarantees that heterogeneous processes will be the dominant pathways for reactions of ions. Explicit reports of ionic chain polymerization in CVD are limited but include the cationic polymerization of isobenzofuran 29–31…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a plasma, the large energetic barrier to creating charged species in the gas phase guarantees that heterogeneous processes will be the dominant pathways for reactions of ions. Explicit reports of ionic chain polymerization in CVD are limited but include the cationic polymerization of isobenzofuran 29–31…”
Section: Introductionmentioning
confidence: 99%
“…Methods for the solution-based polymerization of IBF often result in many undesirable byproducts and low molecular weight polymers due to the very poor stability of IBF and its derivatives. Recently, we demonstrated that poly(isobenzofuran) (PIBF) can be prepared as high-quality polymer thin films by thermal CVD and hot-filament CVD (HFCVD) processes , and discovered that the growth of PIBF is surface-dependent. Specifically, the growth rate of PIBF films grown by the CVD process can be greatly affected by surface functional groups with different acidities present on the target substrates.…”
Section: Introductionmentioning
confidence: 99%